1997
DOI: 10.1007/bf02778196
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, magnesium, and zinc status in experimental hyperthyroidism

Abstract: In this study, experimental hyperthyroidism was established and used to investigate possible alterations in the calcium (Ca), magnesium (Mg), and zinc (Zn) homeostasis by assessing their concentrations in plasma and erythrocytes. In the L-thyroxine-induced hyperthyroidism condition, the experimental animals show a significant decrease in erythrocyte Ca, Mg, and Zn concentrations, and a significant decrease in plasma Mg concentration. Significant positive correlations were found for Mg and Zn both in plasma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…Measurements conducted immediately after the operation also showed lower serum zinc and The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 2 Pre-operative serum element levels of the cases Groups The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 4 Post-operative serum element levels of the cases Groups selenium values than the control groups. There are several studies showing a correlation between zinc defect and thyroid hormone levels [16,19,20]. Zinc is an indispensable element in the functioning of 1,5′-deiodinase, which is necessary for the conversion of T 4 to T 3 [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements conducted immediately after the operation also showed lower serum zinc and The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 2 Pre-operative serum element levels of the cases Groups The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 4 Post-operative serum element levels of the cases Groups selenium values than the control groups. There are several studies showing a correlation between zinc defect and thyroid hormone levels [16,19,20]. Zinc is an indispensable element in the functioning of 1,5′-deiodinase, which is necessary for the conversion of T 4 to T 3 [6].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Kralik and colleagues [13] established that selenium and zinc were important for the thyroid hormone metabolism and the deficiency of these elements would produce a negative impact on thyroid activity. Thyroid cancer patients were also reported to suffer from significantly lower levels of magnesium after the surgical operation [14,15] and experimental hyperthyroidism cases were shown to have lower magnesium levels than their controls both in the erythrocytes and plasma [16]. Altered thyroid activity was claimed to affect copper metabolism as well [2,17].…”
Section: Introductionmentioning
confidence: 96%
“…Third, in the Ames and Snell long-lived dwarf mice, multiple endocrine pathways are disrupted, and it is possible that MT expression is influenced by deficiencies in thyroid stimulating hormone (TSH) or prolactin (PRL) and their effects on zinc metabolism (Figure 4). For instance, hyperthyroidism in humans is associated with altered plasma and erythrocyte zinc concentration (Zhang et al, 2004), and in rats, experimental induction of hyperthyroidism by injection of L-thyroxine leads to decreased zinc erythrocyte concentrations (Simsek et al, 1997). Hyperprolactinemic patients have reduced plasma zinc levels and other studies support an inverse and mutual regulatory relationship between PRL and zinc concentration in plasma (Koppelman, 1988; Madureira et al, 1999).…”
Section: Endocrine Regulation Of Metallothionein In Long-lived Micmentioning
confidence: 99%
“…In contrast, Simsek et al (9) found high erythrocyte zinc levels but could determine no change in plasma zinc levels in hyperthyroidism. The results reported by authors (8,9) cited above seem inconsistent with the studies arguing that the plasma zinc levels increased in hyperthyroidism (10,11). The studies exploring the relationship between hyperthyroidism and zinc show that the consensus has yet to be reached on this topic.…”
mentioning
confidence: 84%
“…It was reported that although intra-erythrocyte zinc levels decreased by 54 % in rats with induced hyperthyroidism, there was no signifi cant change in plasma zinc levels (8). In contrast, Simsek et al (9) found high erythrocyte zinc levels but could determine no change in plasma zinc levels in hyperthyroidism. The results reported by authors (8,9) cited above seem inconsistent with the studies arguing that the plasma zinc levels increased in hyperthyroidism (10,11).…”
mentioning
confidence: 95%